The Legal Politic in Countermeasure the Crime in Funding and Management of Disaster Assistance - Luh Nila Winarni; Cokorde Istri Dian Laksmi Dewi; Anak Agung Gde Raka; Ni Putu Tirka Widanti (Sociological Jurisprudence Journal, 2021)
Indonesian geographical, geological and hydrological regions are disaster-prone areas. Disaster-prone is the geological, biological, hydrological, climatological, geographical, social, cultural, political, economic and technological conditions or characteristics of a region for a certain period of time that reduce the ability in preventing, reducing, achieving readiness, and reduce the ability to respond to adverse impacts of certain hazards. People's behavior that damages the environment also tends to increase the number of disasters. Seeing such conditions, the government has compiled a policy to allocate budgets for pre-disaster, during emergency response, and post-disaster development. This government policy is also supported by the contributions of community in providing disaster relief. A bad disaster management system can be a gap to commit criminal acts against funds and disaster relief. In this study, two issues will be discussed, namely legal politics in funding and managing disaster relief and the legal consequences of criminal acts in funding and management of disaster relief. The legal politics in disaster relief funding and management are outlined in The Act Number 24 of 2007 concerning Disaster Management and Republic of Indonesia Government Regulation Number 22 of 2008 concerning Funding and Management of Disaster Assistance. The legal consequences of criminal acts of funding and management of disaster assistance are criminal penalties ranging from imprisonment, fines, or capital punishment